Hubungan Penggunaan Kekuasaan Keahlian Kepala Sekolah dengan Kinerja Guru SMAN - Patar Rumapea (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
The aim of this study is to find out the influence of principals power on teachers performance. One hundred and forty teachers from ten public senior high school were involved in this study. Data from questionnaires were descriptively analyzed. The results of the study indicate that principals expert power positively correlates with teachers performance. However, the correlation is of low degree due to the fact that principals are perceived to offer teachers with little help.